A versatile small form factor twisted-pair TFC FMC for MTCA AMCs. (21st March 2017) - Meder, L.; Lebedev, J.; Becker, J.
Abstract: In continuous readout systems of particle physics experiments, the provision of a common clock and time reference and the distribution of critical low latency messages to the processing and fronted layers of the readout are crucial tasks. In the context of the Compressed Baryonic Matter (CBM) experiment, a versatile small form factor Timing and Fast-Control (TFC) interfacing FPGA Mezzanine Card (FMC) was developed, offering bidirectional twisted-pair (TP) links for the communication between TFC nodes. Also a versatile clocking including voltage controlled oscillators and a connection to the telecommunication clock lines of mTCA crates are available. Being designed for both TFC Master and Slaves, the card allows rapid system developments without additional Slave hardware circuits. Measurements show that it is possible to transmit over cable lengths of 25 m at a rate of 240 Mbit/s for all data channels simultaneously. A TFC Master-Slave system using two of these cards can be synchronized with a precision of ±10 ps to an user-defined phase setpoint.